Happy Easter. - Wiese, Kurt, 1887-1974. (New York, Viking Press, 1952)
A hen gives the Easter rabbits the eggs she's been sitting on for three weeks and after the rabbits paint them a surprising thing happens.
Mode of access: Internet.